2014
DOI: 10.1002/adma.201304256
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Structure of Nickelates to Achieve Two‐Dimensional Electron Conduction

Abstract: Metallic electronic transport in nickelate heterostructures can be induced and confined to two dimensions (2D) by controlling the structural parameters of the nickel-oxygen planes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
101
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 52 publications
10
101
1
Order By: Relevance
“…Nickel possesses one electron in e g orbit in Ni 3+ state, as illustrated in Fig. 4(d This is similar to the scenario reported in the previous publication, 8,[28][29][30] and a further low-temperature XMCD (x-ray magnetic circular dichroism) is expected to give an insight into the respective contribution to magnetism during the transition. But this is not the case for the 3 u.c.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…Nickel possesses one electron in e g orbit in Ni 3+ state, as illustrated in Fig. 4(d This is similar to the scenario reported in the previous publication, 8,[28][29][30] and a further low-temperature XMCD (x-ray magnetic circular dichroism) is expected to give an insight into the respective contribution to magnetism during the transition. But this is not the case for the 3 u.c.…”
supporting
confidence: 67%
“…10,11 Other important factors such as, charge ordering associated with structural symmetry, and strain induced orbital polarization can also account for MIT. 12, 13 Recently it is found that the capping of ultrathin LaAlO 3 enhanced the conductivity of ultrathin LaNiO 3 , 8 reflecting the critical role of the capping effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polar and/or oxygen octahedral distortions occurring on the free surface of LNO are known to deteriorate the metallic conductivity of the nickelate films. 38 The effect of capping the LNO layers with LMO (= sharp interface configuration) suppresses such distortions and improves conductivity (blue vs. grey curve in Figure 2b). Confirming this scenario, the relative enhancement increase of conductivity of the capped LNO-layer compared to the equivalently thick non-capped LNO film is found to be more significant for low period bilayers, (i.e.…”
Section: Abstract: Interface Engineering Manganites Nickelates Magmentioning
confidence: 99%
“…directly correlates to the material's resulting properties. [1][2][3][4][5] For example, systems such as the manganites (colossal magnetoresistance), 6 the cobaltates (spin-state transitions), 7,8 and the cuprates (hightemperature superconductivity) 9,10 owe their behaviors to specific configurations of the electronically active transition-metal cation d orbitals, which, for near-cubic symmetry, are split into the (lower energy) t 2g and (higher energy) e g orbitals. The development of atomically precise growth techniques for oxides has opened up the possibility of controlling orbital configurations via layered heterostructures.…”
Section: Introductionmentioning
confidence: 99%